Bonding composition for battery packaging material, metal composite film, soft package shell and battery
By using a bonding composition of acid-modified polypropylene and specific additives, the problem of insufficient heat resistance and corrosion resistance of the dry-process metal composite film in high temperature environments is solved, stable coating of battery packaging materials and stability of the internal chemical system of the battery are achieved, and the safety and durability of the battery are improved.
Patent Information
- Application Number
- CN202510620646.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-14
- Publication Date
- 2025-08-08
AI Technical Summary
The existing dry-process metal composite films have insufficient heat resistance, corrosion resistance and durability in high temperature environments, resulting in battery safety and chemical system stability issues, which cannot meet the needs of all-solid-state batteries.
The bonding composition formed by acid-modified polypropylene is used as the binder and combined with a specific additive has at least two melting peaks to ensure that the inner bonding layer does not form a pudding shape at high temperatures, achieve stable processing and coating, and optimize composition performance by differential scanning calorimetry (DSC).
It improves the high temperature resistance, corrosion resistance and durability of the metal composite film, ensures the stable operation of the internal chemical system of the battery, and enhances the safety and reliability of the battery.
Smart Images

Figure CN120442194A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal laminate films, and in particular to an adhesive composition for battery packaging materials, a metal composite film, a soft package shell and a battery. Background Art
[0002] Currently, lithium-ion batteries are mainly divided into three categories: square, cylindrical, and soft-pack. Square and cylindrical batteries are mainly made of hard shells such as aluminum alloy and stainless steel, which makes the design of hard-pack batteries inflexible. Soft-pack batteries, on the other hand, use metal composite films for their shells, which greatly improves the design flexibility of hard-pack batteries.
[0003] There are two main types of metal composite films. The first is a dry-process product, which consists of an outer base resin layer, an outer adhesive layer, an intermediate metal layer, an inner bonding layer, and a heat-sealing resin layer. The second is a thermal-process product, which, from the outside to the inside, consists of an outer base resin layer, an outer adhesive layer, an intermediate metal layer, and an inner heat-sealing resin layer. This product is used as a battery outer packaging material.
[0004] At present, higher requirements are being placed on the high temperature resistance, corrosion resistance, durability and safety of battery outer packaging materials. Due to the presence of the inner adhesive layer, the high temperature resistance of dry-process products is lower than that of hot-process products. There are several main reasons for this: (1) Dry-process products mainly use polypropylene and isocyanate curing agents to prepare the inner adhesive layer. However, the melting point of polypropylene is between 70℃ and 80℃, so the heat resistance is low at a high temperature of 120℃. (2) When the existing high-melting-point resin is dissolved and then combined with the curing agent, it often forms a pudding-like shape within 3 minutes, and then it cannot be coated and bonded, and it cannot be processed to produce mass products. (3) If modified polypropylene is used, the acid grafting rate of modified polypropylene is low, generally below 2%. Therefore, hydrolysis occurs during storage, which leads to insufficient units for cross-linking reaction with the curing agent, and ultimately leads to defects in the heat resistance, corrosion resistance, durability and safety of the metal composite film.
[0005] In summary, dry-process metal composite membranes have poor high-temperature resistance, corrosion resistance, and durability. When stored at high temperatures, electrolyte swelling and electrolyte penetration occur, reducing the stability of the battery's internal chemical system. In severe cases, bulging and cracking may occur, seriously affecting safety. High-temperature heat sealing performance is also poor, making it unable to meet the requirements of next-generation all-solid-state batteries.
[0006] In view of this, the present invention is proposed. Summary of the Invention
[0007] The present invention aims to provide an adhesive composition, metal composite film, soft-pack casing, and battery for battery packaging. Embodiments of the present invention provide an adhesive composition with excellent processing and usability, preventing pudding-like formation and enabling stable processing and coating. Furthermore, the metal composite film formed using the adhesive composition exhibits excellent packaging performance, high-temperature resistance, corrosion resistance, durability, and insulation properties in high-temperature electrolyte environments, ensuring stable operation of the battery's internal chemical system.
[0008] The present invention is achieved in that:
[0009] In a first aspect, the present invention provides an adhesive composition for battery packaging materials, the raw materials of which include acid-modified polypropylene and an additive, wherein the acid-modified polypropylene exhibits at least two melting peaks during the heating process when tested by differential scanning calorimetry (DSC), specifically manifested as follows:
[0010] (1) The endothermic temperature of the first main melting peak, TmAp1, ranges from 135 to 170 °C, and its corresponding peak area is recorded as Ap_1;
[0011] (2) The endothermic temperature of the second melting peak, TmAp2, ranges from 75 to 130 °C, and its corresponding peak area is recorded as Ap_2;
[0012] (3) The area ratio of the peak area Ap_2 of the second melting peak to the peak area Ap_1 of the first main melting peak satisfies: Ap_2 / Ap_1≤60%.
[0013] In an alternative embodiment,
[0014] The temperature of the top peak in the endothermic temperature band of the first main melting peak is set as TAp_1, and TAp_1 is above 140°C;
[0015] The temperature of the top peak in the endothermic temperature band of the peak temperature of the second melting peak is defined as TAp_2, and TAp_2 is 99.6°C or higher.
[0016] In an optional embodiment, the calorific value of the acid-modified polypropylene during the heating time is measured by differential scanning calorimetry with the heating condition set at 5-10°C / min.
[0017] In an optional embodiment, the raw materials are composed of acid-modified polypropylene, epoxy curing agent, phosphite containing hindered aromatic group, phenolic antioxidant, lubricant and crystallization accelerator; or
[0018] Its raw materials are composed of acid-modified polypropylene and isocyanate curing agent.
[0019] In an optional embodiment, the hindered aromatic group-containing phosphite is selected from at least one of octadecanol-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, bis(2,4-di-tert-butylphenol) pentaerythritol diphosphite, tris(2,4-di-tert-butyl)phenyl phosphite, (2,4,6-tri-tert-butylphenyl-2-butyl-2-ethyl)-1,3,2,2'-ethylenebis(4,6-di-tert-butylphenyl) fluorophosphite, tetrakis(2,4-di-tert-butyloctaalkoxy-4,4-biphenyl) phosphate and spiroethylene glycol di[2,2'-methylenebis(4,6-di-tert-butylphenyl)]phosphite; preferably at least one of octadecanol-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and tris(2,4-di-tert-butyl)phenyl phosphite;
[0020] Preferably, the amount of the hindered aromatic phosphite is 0.05-0.35 parts per 100 parts of the acid-modified polypropylene, in parts by weight;
[0021] Preferably, based on parts by weight, for every 100 parts of the acid-modified polypropylene, the amount of octadecanol-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate is 0.05-0.2 parts, and the amount of tris(2,4-di-tert-butyl)phenyl phosphite is 0.05-0.15 parts.
[0022] In an optional embodiment, the phenolic antioxidant includes at least one of N,N"-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, 3-(3,5-di-tert-butyl-4-hydroxy)-N"-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]propionohydrazide, 2,6-di-tert-butyl-4-methylphenol, bis(3,5-di-tert-butyl-4-hydroxyphenyl)sulfide, tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester and tert-butylhydroquinone; preferably tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester;
[0023] Preferably, the amount of the phenolic antioxidant is less than 0.1 parts by weight per 100 parts by weight of the acid-modified polypropylene.
[0024] In an optional embodiment, the lubricant is selected from at least one of amide derivatives, diatomaceous earth, talc, silicon dioxide, calcium carbonate, calcium sulfate, organosiloxane compounds and stearates; more preferably at least one of oleamide, erucamide, calcium stearate and polyethylene wax;
[0025] Preferably, the amount of the lubricant is 0.1-0.6 parts by weight per 100 parts of the acid-modified polypropylene.
[0026] In an optional embodiment, the crystallization promoter is at least one selected from the group consisting of metal phosphates, basic metal phosphates, and composites thereof, preferably sodium 2,2"-methylenebis(4,6-di-tert-butylphenyl) phosphate and basic aluminum 2,2"-methylenebis(4,6-di-tert-butylphenyl phosphate); more preferably sodium 2,2"-methylenebis(4,6-di-tert-butylphenyl) phosphate;
[0027] Preferably, the amount of the crystallization accelerator is 0.02-0.1 parts per 100 parts of the acid-modified polypropylene, calculated by weight.
[0028] In an optional embodiment, the epoxy curing agent is selected from at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, phenol-type novolac epoxy, o-cresol-type novolac epoxy, trisphenol methane-type and tetraphenol ethane-type epoxy, polyphenol-type glycidyl ether epoxy resin, aliphatic glycidyl ether epoxy resin and glycidyl ester epoxy resin, preferably at least one of bisphenol A epoxy resin, bisphenol F epoxy resin and novolac epoxy resin, more preferably bisphenol F epoxy resin and novolac epoxy resin;
[0029] Preferably, the epoxy curing agent is used in an amount of 2-15 parts by weight for every 100 parts of the acid-modified polypropylene.
[0030] In an optional embodiment, the epoxy value of the epoxy curing agent is 0.2 mol / 100 g-2.0 mol / 100 g;
[0031] Preferably, the mass ratio of the bisphenol F epoxy resin to the novolac epoxy resin is (7-10):1.
[0032] In an optional embodiment, the isocyanate curing agent is selected from at least one of hexamethylene diisocyanate or pentamethylene diisocyanate containing more than 50%;
[0033] Preferably, the amount of the isocyanate curing agent used is 1-4 parts by weight for every 100 parts of the acid-modified polypropylene.
[0034] In an optional embodiment, the SP value of the bonding composition is 7.6-8.6;
[0035] Preferably, the dissolution temperature of the bonding composition is 60-70°C.
[0036] In a second aspect, the present invention provides a metal composite film for battery packaging materials, which includes an outer layer, an outer adhesive layer, a metal layer, an inner adhesive layer and a hot-melt resin layer arranged in sequence, wherein the inner adhesive layer is prepared by the adhesive composition for battery packaging materials described in any one of the aforementioned embodiments.
[0037] In a third aspect, the present invention provides a soft package shell, which is prepared by the metal composite film for battery packaging material described in the aforementioned embodiment.
[0038] In a fourth aspect, the present invention provides a battery comprising the soft-pack casing described in the aforementioned embodiment.
[0039] The present invention has the following beneficial effects: The embodiments of the present invention utilize a specific acid-modified polypropylene as the primary raw material for preparing the adhesive, which, when reacted with a curing agent, results in an inner adhesive layer having excellent heat resistance and flexibility. Furthermore, the specific acid-modified polypropylene does not form a pudding-like consistency when combined with the curing agent, thereby facilitating the processing and coating of the adhesive composition. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other relevant drawings can be obtained based on these drawings without paying any creative work.
[0041] Figure 1 The DSC chart of the acid-modified polypropylene provided in Example 1 of the present invention;
[0042] Figure 2 The DSC graph of the acid-modified polypropylene provided in Comparative Example 1 of the present invention;
[0043] Figure 3 These are the performance test results of the metal composite films of Examples 1-3 of the present invention and Comparative Examples 1-3. DETAILED DESCRIPTION
[0044] To make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer are used. Where the manufacturer of the reagents or instruments is not specified, all are conventional products that can be purchased commercially.
[0045] In the first aspect, the present invention provides an adhesive composition for battery packaging materials, which is mainly used to prepare the inner adhesive layer of a metal composite film. The adhesive composition is not easy to form a pudding shape during use, can be stably coated and processed, and the inner adhesive layer formed by it has good high temperature resistance, corrosion resistance and durability.
[0046] Specifically, the bonding composition includes acid-modified polypropylene and additives. The acid-modified polypropylene is different from existing conventional polypropylene. The acid-modified polypropylene has a molecular weight of about 100,000 and has at least two melting peaks, one of which is much higher than the melting peak of conventional polypropylene, thereby achieving high temperature resistance.
[0047] The two melting peaks are determined by measuring the heat generated by the acid-modified polypropylene during heating time using differential scanning calorimetry, and observing endothermic activity of the acid-modified polypropylene at at least two locations. Specifically, (1) the endothermic temperature range of the first main melting peak (TmAp1) is 135-170°C; for example, any value between 135-170°C, such as 135°C, 140°C, 150°C, 155°C, 165°C, and 170°C, preferably above 140°C. The corresponding peak area is recorded as Ap_1.
[0048] (2) The endothermic temperature range of the second melting peak (TmAp2) is 75-130°C; for example, any number between 75-130°C, such as 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 110°C, 120°C, and 130°C, preferably above 99.6°C. The corresponding peak area is recorded as Ap_2.
[0049] (3) The area ratio of the peak area Ap_2 of the second melting peak to the peak area Ap_1 of the first main melting peak satisfies Ap_2 / Ap_1≤60%.
[0050] Furthermore, the temperature of the top peak in the endothermic temperature band of the first main melting peak is set to TAp_1, and TAp_1 is 140°C or higher.
[0051] The temperature of the top peak in the endothermic temperature band of the peak temperature of the second melting peak is defined as TAp_2, and TAp_2 is 99.6°C or higher.
[0052] Specifically, the calorific value of the acid-modified polypropylene during the heating time is measured by differential scanning calorimetry with the heating condition set at 5-10° C. / min.
[0053] The acid-modified polypropylene can be purchased directly, for example, from Mitsui or Nippon Paper.
[0054] Furthermore, the adhesive composition provided in the embodiments of the present invention can have a variety of formulations, as long as it contains the acid-modified polypropylene. The embodiments of the present invention are illustrated by the following two formulations.
[0055] Formula 1: Its raw materials are composed of acid-modified polypropylene, epoxy curing agent, phosphite containing hindered aromatic group, phenolic antioxidant, lubricant and crystallization accelerator.
[0056] The addition of hindered aromatic phosphites can decompose and subsequently eliminate residual initiators in synthetic acid-modified polypropylene. Specifically, hindered aromatic phosphites not only decompose hydroperoxides but also function as chain terminators. Research and practice have demonstrated that hindered groups around the P atom significantly improve heat resistance and hydrolysis resistance. Hindered aromatic phosphites not only decompose hydroperoxides but also function as chain terminators. Research and practice have demonstrated that hindered groups around the P atom significantly improve heat resistance and hydrolysis resistance.
[0057] Specifically, the hindered aromatic group-containing phosphite is selected from at least one of octadecanol-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, bis(2,4-di-tert-butylphenol)pentaerythritol diphosphite, tris(2,4-di-tert-butyl)phenyl phosphite, (2,4,6-tri-tert-butylphenyl-2-butyl-2-ethyl)-1,3,2,2'-ethylenebis(4,6-di-tert-butylphenyl)fluorophosphite, tetrakis(2,4-di-tert-butyloctaalkoxy-4,4-biphenyl) phosphate and spiroethylene glycol di[2,2'-methylenebis(4,6-di-tert-butylphenyl)]phosphite; preferably, it is at least one of octadecanol-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and tris(2,4-di-tert-butyl)phenyl phosphite.
[0058] The amount of the hindered aromatic group-containing phosphite used is 0.05-0.35 parts per 100 parts of the acid-modified polypropylene, for example, the amount of octadecanol-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate used is 0.05-0.2 parts, and the amount of tris(2,4-di-tert-butyl)phenyl phosphite used is 0.05-0.15 parts per 100 parts of the acid-modified polypropylene, for example.
[0059] Phenolic antioxidants can also decompose residual initiators in acid-modified polypropylene. Specifically, phenolic antioxidants are compounds with substituents on one or both sides of the hydroxyl group (-OH) on the benzene ring. Due to steric hindrance, the H atom easily falls off the molecule and combines with peroxide free radicals (ROO.), alkoxy free radicals (RO.), hydroxyl free radicals (.OH), etc., rendering them inactive, thereby terminating the chain reaction of thermal oxidative aging. There is a synergistic effect when phenolic antioxidants are compounded with phosphites. As the primary antioxidant, phenolic antioxidants contain active hydrogen atoms (O-H). These hydrogen atoms are more active than the hydrogen atoms on the carbon chain of acid-modified polypropylene (including hydrogen atoms on double bonds on the carbon chain). They can be separated and combine with the acid-modified polypropylene free radicals R. or R00. to generate hydrogen peroxide and stable phenoloxy free radicals (ArO.). Because the increase of the ortho-substituent number of the phenoloxy free radical or the increase of its branching, promptly increase its steric hindrance effect, just can make it be protected by adjacent larger-volume group like this, improved the stability of phenoloxy free radical.In addition, because the phenyl ring of phenolic antioxidant is in large conjugated system together with phenoloxy free radical, thereby more stable, activity is lower, can not trigger chain reaction, can only combine with another active free radical, stop a free radical again, generate more stable compound, thereby stop chain reaction.This stability of phenoloxy free radical can prevent antioxidant from being consumed too fast because of direct oxidation, and can also reduce chain transfer reaction, thereby improve its antioxidant property.
[0060] Specifically, phenolic antioxidants include, but are not limited to, at least one of N,N"-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, 3-(3,5-di-tert-butyl-4-hydroxy)-N"-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]propionohydrazide, 2,6-di-tert-butyl-4-methylphenol, bis(3,5-di-tert-butyl-4-hydroxyphenyl)sulfide, tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester and tert-butylhydroquinone; preferably tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester.
[0061] Furthermore, based on parts by weight, the amount of the phenolic antioxidant used is less than 0.1 parts per 100 parts of the acid-modified polypropylene.
[0062] During PP polymerization or anhydride grafting, initiators are added. These initiators are all peroxides, which are the source of free radical reactions. If residual initiator is left in the PP for a long time, it will continue to cause chain growth, resulting in larger crystals and a pudding-like shape. Furthermore, it prevents the polymer from reacting with oxygen molecules and the anhydride from hydrolyzing into carboxylic acid. Because carboxylic acid has high polarity and acts as a pendant group, it can form hydrogen bonds or enhance intermolecular forces, promoting crystallization and a pudding-like shape.
[0063] Lubricants, on the other hand, prevent adhesion and precipitation, improve leveling, and provide both external and internal slip. They dissolve in the solvent at high temperatures and precipitate during cooling to room temperature, existing in the coating as microcrystals. Their thixotropic properties make the resin more easily open under applied shear forces, reducing system viscosity and improving fluidity. On the one hand, they provide a lubricating effect, physically preventing the close proximity of crystallized spherulites, preventing the formation of large spherulites and acting as an isolation barrier. On the other hand, lubricants are lubricants that are difficult to decompose at high temperatures. Heterogeneous nucleation occurs by adsorbing polymer chains in the melt onto foreign impurities, incompletely melted residual crystalline polymer, dispersed small solid particles, or the walls of the container, forming crystal nuclei that are arranged in an orderly manner. This refines the crystals and prevents the formation of a pudding-like structure.
[0064] Specifically, the embodiments of the present invention utilize lubricants with a low melting point, first melting into a liquid state. These lubricants then act as internal lubricants, entering the unmelted resin particles or coating the resin particles' surfaces as external lubricants. While the melted resin appears to be dissolved in the liquid resin phase from a macroscopic perspective, this is not a true solution and is not uniformly distributed across the surface. Microscopically, the lubricant still forms an interface with the liquid resin phase. The lubricant-resin mixture exists as microcrystals within the resin solution.
[0065] Specifically, the lubricant includes, but is not limited to, at least one of amide derivatives, diatomaceous earth, talc, silicon dioxide, calcium carbonate, calcium sulfate, organosiloxane compounds and stearates; more preferably at least one of oleamide, erucamide, calcium stearate and polyethylene wax.
[0066] Furthermore, the amount of the lubricant is 0.1-0.6 parts by weight for every 100 parts of the acid-modified polypropylene.
[0067] Furthermore, the crystallization promoter induces crystallization, adsorbs the acid-modified polypropylene to form more fine crystal nuclei, reduces the spherulite size of the acid-modified polypropylene, and improves smoothness and fluidity. In the embodiment of the present invention, the crystallization promoter is selected from at least one of phosphate metal salts, phosphate ester basic metals, and their combinations, including, but not limited to, sodium 2,2"-methylenebis(4,6-di-tert-butylphenyl) phosphate and basic aluminum 2,2"-methylene-bis(4,6-di-tert-butylphenyl phosphate); more preferably, sodium 2,2"-methylenebis(4,6-di-tert-butylphenyl) phosphate.
[0068] Furthermore, the amount of the crystallization accelerator is 0.02-0.1 parts per 100 parts of the acid-modified polypropylene, calculated in parts by weight.
[0069] Furthermore, the epoxy curing agent is selected from at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, phenol-type novolac epoxy, o-cresol-type novolac epoxy, trisphenol methane-type and tetraphenol ethane-type epoxy, polyphenol-type glycidyl ether epoxy resin, aliphatic glycidyl ether epoxy resin, and glycidyl ester epoxy resin, preferably at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, and novolac epoxy resin, more preferably bisphenol F epoxy resin and novolac epoxy resin. The mass ratio of bisphenol F epoxy resin to the novolac epoxy resin is (7-10):1. The epoxy value of the epoxy curing agent is 0.2 mol / 100g-2.0 mol / 100g; its molecular weight is 100-1000.
[0070] Furthermore, the epoxy curing agent is used in an amount of 2-15 parts by weight for every 100 parts of the acid-modified polypropylene;
[0071] Formula 2: The raw materials are composed of acid-modified polypropylene and an isocyanate curing agent. The isocyanate curing agent is selected from at least one of hexamethylene diisocyanate (HDI) or pentamethylene diisocyanate (PDI) containing at least 50%. The ratio of the COOH value of the acid-modified polypropylene to the NCO value of the curing agent is NCO / COOH = 1.36 to 4.32, preferably NCO / COOH = 3.6. The amount of the isocyanate curing agent is 1-4 parts per 100 parts of the acid-modified polypropylene.
[0072] Furthermore, the dissolution temperature of the bonding composition is 60-70°C. The bonding composition is generally prepared as a masterbatch first, and then melted for use when in use. Therefore, it is necessary to limit its dissolution stability. If it is below 60°C, it cannot be dissolved and used in a short time. Above 70°C, the lubricant will migrate into the resin, and it will be impossible to achieve the residual crystalline acid-modified polypropylene that is not completely melted, the dispersed small particles of solid or the wall of the container as the center, and the polymer chains in the melt are adsorbed to form a crystal nucleus in an orderly arrangement, making the crystals finer and preventing the formation of a pudding-like shape. Once a pudding-like shape is formed, coating production cannot be achieved. The resin needs to be dissolved strictly according to this temperature. In addition, the constant temperature of 60°C is maintained during the coating process to prevent the reaction and solidification from starting during the coating process. Therefore, the coating amount of the metal layer is unstable and the physical properties are unstable.
[0073] Of course, it is understandable that the raw materials may be directly mixed in proportion and used instead of being prepared as master batches.
[0074] Furthermore, the bonding composition is dissolved in an organic solvent, including but not limited to cyclohexane, methylcyclohexane, butanone, hexylbenzene, toluene, and o-xylene. For example, a mixed solvent of cyclohexane, butanone, and hexylbenzene may be used, wherein the volume ratio of the three solvents is 7:2:1. The SP value of the bonding composition is adjusted to 7.6-8.6.
[0075] Furthermore, the present invention provides a metal composite film for battery packaging materials, which includes an outer layer, an outer adhesive layer, a metal layer, an inner adhesive layer and a hot-melt resin layer arranged in sequence, wherein the inner adhesive layer is prepared by the adhesive composition for battery packaging materials described in any one of the aforementioned embodiments.
[0076] In a third aspect, the present invention provides a soft package shell, which is prepared by the metal composite film for battery packaging material described in the aforementioned embodiment.
[0077] In a fourth aspect, the present invention provides a battery comprising the soft-pack casing described in the aforementioned embodiment.
[0078] The testing method of the metal composite film according to the embodiment of the present invention is as follows:
[0079] (1) Electrolyte peeling strength
[0080] Cut a number of thin strips (MD: 100-120mm, TD: 15mm) to be soaked in the same number of days of electrolyte solution. Bundle the strips with PP or PET film, securing them 20% of the way down (soaking the bundled area can lead to uneven test results). In a dry room, pour electrolyte into a storage container. Roll the tightly bound strips into a coil and place them horizontally at the bottom of the container, ensuring the liquid level is at least 20mm above the strips. Place the container containing the strips in a standard aluminum bag (to prevent excess moisture and leakage) and then place it in an 85°C oven for the desired number of days. After removing the strips from the bottle, cool them in a dry room to room temperature. Remove the bundled strips from the bottle and wipe them with lint-free paper to absorb any excess electrolyte. Half-fill a bucket with water, unwrap the bundled strips, and submerge them in the bucket. Turn on the tap again and rinse with running water for 15 minutes. After removing the specimen from the water, dry it with dust-free paper and start the tensile testing. The experimental conditions (test speed 50 mm / min, test distance 50 mm, 10 mm before and after the data are discarded, the effective value range is 20-40 mm. Record the average value.
[0081] (2) 120℃ high temperature heat seal strength
[0082] Cut a sample 200 mm in the MD direction and 76 mm in the TD direction. Fold the sample in half along the MD direction and heat seal it in the MD direction using the following heat sealing conditions: heat sealing temperature 190°C (constant), heat sealing pressure 1.0 MPa, and heat sealing time 3 seconds. Cut three 15 mm wide samples (n=3) from the center of the heat-sealed sample, with the cutting line perpendicular to the heat sealing line. Turn on the stretching machine and set the clamp distance to 50 mm, the stretching speed to 300 mm / min, the measuring stroke to 30 mm, and the set temperature to 120°C. The value is taken as the maximum value of the entire stroke.
[0083] The features and performance of the present invention are further described in detail below with reference to the embodiments.
[0084] Example 1
[0085] An embodiment of the present invention provides an adhesive composition for battery packaging materials, wherein the raw materials of the adhesive composition are composed of acid-modified polypropylene, an epoxy curing agent, a phosphite containing a hindered aromatic group, a phenolic antioxidant, a lubricant, and a crystallization accelerator.
[0086] The acid-modified polypropylene had a weight-average molecular weight of 97,000 and two melting peaks. These two melting peaks were observed when a differential scanning calorimeter was used to measure the calorific value relative to the heating time at a temperature increase of 10°C / min and at least two locations exhibited endothermic activity derived from the acid-modified polypropylene.
[0087] Specifically, the endothermic temperature TmAp1 of the first main melting peak ranges from 135 to 170°C, and its corresponding peak area is recorded as Ap_1; the temperature of the top peak in the endothermic temperature band of the first main melting peak is set as TAP_1, and TAP_1 is 158.38°C. The endothermic temperature TmAp2 of the second melting peak ranges from 75 to 130°C, and its corresponding peak area is recorded as Ap_2; the temperature of the top peak in the endothermic temperature band of the peak temperature of the second melting peak is set as TAP_2, and TAP_2 is 104.3°C. Ap_2 / Ap_1 is 45%. TmAp1 is 135 to 170°C; TmAp2 is 75 to 130°C. Specifically, its DSC diagram can be found in Figure 1 .
[0088] The preparation method for this acid-modified polypropylene is as follows: melt grafting is employed. The melt grafting method has been a common method for grafting modified PP in recent years. This process involves co-extrusion of PP and maleic anhydride (MAH) initiator under certain conditions. The reaction takes place above the melting point of PP, typically at 190-230°C. The reaction is simple to operate and requires no solvent recovery, enabling industrial continuous production. However, due to the high reaction temperature, the PP chain is prone to scission, resulting in significant degradation of macromolecular free radicals in the melt-grafted PP system with small molecule initiators (such as diisobutylene peroxide), making the reaction difficult to control. The product also suffers from a low grafting rate, unstable material properties, and a short residence time. The MAH grafting reaction is inefficient, resulting in a low grafting rate. Furthermore, the corrosion of MAH on extrusion equipment limits the commercial production of MAH-grafted polyolefins (PP-g-MAH).
[0089] The mass ratio of acid-modified polypropylene to epoxy curing agent is 100:4. The epoxy curing agent is a mixture of bisphenol F epoxy resin and novolac epoxy resin in a mass ratio of 9:1. The hindered aromatic phosphites are octadecanol-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and tris(2,4-di-tert-butyl)phenyl phosphite. For every 100 parts of acid-modified polypropylene, the amount of octadecanol-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and tris(2,4-di-tert-butyl)phenyl phosphite is 0.1 part. The lubricants are calcium stearate and polyethylene wax, with the amount of calcium stearate being 0.2 part and the amount of polyethylene wax being 0.2 part. The crystallization accelerator is sodium 2,2'-methylenebis(4,6-di-tert-butylphenyl) phosphate, with the amount being 0.05 part. The amount of the phenolic antioxidant pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate is 0.05 parts.
[0090] The bonding composition had a melting temperature of 60° C. and an SP value of 8.0.
[0091] An embodiment of the present invention provides a method for preparing an adhesive composition for battery packaging materials, comprising: mixing the above raw materials according to a certain proportion.
[0092] An embodiment of the present invention provides a metal composite film for battery packaging materials, which includes an outer layer, an outer adhesive layer, a metal layer, an inner adhesive layer and a hot-melt resin layer arranged in sequence, wherein the inner adhesive layer is prepared by the above-mentioned adhesive composition.
[0093] An embodiment of the present invention provides a method for preparing a metal composite film for battery packaging material, comprising:
[0094] A biaxially oriented 25μm nylon membrane was laminated to a 35μm thick 8021 aluminum foil with a surface wettability of 68 dyn / cm via an outer layer of adhesive. Both sides of the aluminum foil were treated with an anti-corrosion solution to form an anti-corrosion layer. The ratio of trivalent chromium compound, inorganic acid, and organic resin on the aluminum foil surface was 2:2:1. The trivalent chromium compound was chromium phosphate, the inorganic acid was nitric acid, and the organic resin was polyacrylic acid.
[0095] The bonding composition is applied to the anti-corrosion treated metal surface of the composite film compounded with the outer substrate resin, and after drying, an inner bonding layer with a thickness of 2 μm is formed. Thereafter, the bonding layer is thermally compounded with the bonding surface of the 40 μm hot melt resin at a temperature of 140°C, and then heat treated at a temperature of 190°C for 1 minute to form a metal composite film of outer substrate resin layer (i.e., outer layer) (25 μm) / outer adhesive layer (3 μm) / metal layer / inner bonding layer / hot melt resin layer (40 μm).
[0096] Performance test results:
[0097] After 14 days of storage at 85°C in an electrolyte containing 1000ppm water, the metal composite film demonstrated an electrolyte peel strength of 12.398N. After 28 days of storage, the peel strength remained at 5.19N, demonstrating excellent electrolyte resistance. Heat seal strength was measured at 120°C for 5 minutes, with a seal strength retention rate of 49%. This demonstrates excellent high-temperature resistance.
[0098] Example 2
[0099] An embodiment of the present invention provides an adhesive composition for battery packaging materials, wherein the raw materials of the adhesive composition are composed of acid-modified polypropylene, an epoxy curing agent, a phosphite containing a hindered aromatic group, a phenolic antioxidant, a lubricant, and a crystallization accelerator.
[0100] The acid-modified polypropylene has a weight-average molecular weight of 102,000 and two melting peaks: TAp_1 of 155.9°C, TAp_2 of 103°C, Ap_2 / Ap_1 of 50%, TmAp1 of 135-170°C, and TmAp2 of 75-130°C.
[0101] The preparation method for this acid-modified polypropylene is as follows: The polypropylene is first dissolved in a boiling toluene, xylene, or benzene solution at 100-140°C, followed by the addition of monomers and a flammable agent for grafting. The grafted product is then extracted with acetone to remove unreacted monomers, forming the final product. This method offers a low reaction temperature, minimal side reactions, low PP degradation, and high grafting efficiency. The method is simple and suitable for small-batch production.
[0102] The mass ratio of acid-modified polypropylene to epoxy curing agent is 100:4. The epoxy curing agent is a mixture of bisphenol F epoxy resin and novolac epoxy resin in a mass ratio of 9:1. The hindered aromatic phosphites are octadecanol-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and tris(2,4-di-tert-butyl)phenyl phosphite. For every 100 parts of acid-modified polypropylene, the amount of octadecanol-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate is 0.1 part, and the amount of tris(2,4-di-tert-butyl)phenyl phosphite is 0.15 part. The lubricants are calcium stearate and erucamide, with the amount of calcium stearate being 0.25 part and the amount of erucamide being 0.05 part. The crystallization promoter is sodium 2,2'-methylenebis(4,6-di-tert-butylphenyl) phosphate, and the amount used is 0.05 parts. The amount used of the phenolic antioxidant pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate is 0.08 parts.
[0103] The bonding composition had a melting temperature of 65° C. and an SP value of 8.0.
[0104] In this embodiment, a metal composite film is prepared by referring to the preparation method of the metal composite film provided in Example 1, with the only difference being that the inner bonding layer is prepared using the bonding composition provided in this embodiment.
[0105] Performance test results of the metal composite film:
[0106] The metal composite film exhibited excellent electrolyte resistance after being stored at 85°C for 14 days in an electrolyte containing 1000ppm water. The peel strength was 11.47N after 28 days of storage, reaching 3.3N. Heat seal strength was also tested at 120°C for 5 minutes, reaching 66.36N, with a seal strength retention rate of 49%. This demonstrates excellent high-temperature resistance.
[0107] Example 3
[0108] An embodiment of the present invention provides an adhesive composition for battery packaging materials, wherein the raw materials of the adhesive composition are composed of acid-modified polypropylene, an epoxy curing agent, a phosphite containing a hindered aromatic group, a phenolic antioxidant, a lubricant, and a crystallization accelerator.
[0109] The acid-modified polypropylene has a weight-average molecular weight of 68,000, a TAp_1 of 160.5°C, a TAp_2 of 101.7°C, an Ap_2 / Ap_1 ratio of 58%, a TmAp1 of 135-170°C, and a TmAp2 of 75-130°C.
[0110] The preparation method of the acid-modified polypropylene is as follows:
[0111] Melt grafting has been a common method for grafting and modifying PP in recent years. This process involves co-extrusion of PP and maleic anhydride (MAH) initiator under specific conditions. The reaction occurs above the melting point of PP, typically at 190-230°C. This reaction is simple to operate and requires no solvent recovery, enabling industrial continuous production. However, due to the high reaction temperature, the PP chain is prone to scission, leading to significant degradation of macromolecular free radicals in melt-grafted PP systems with small molecule initiators (such as diisobutylene peroxide), making the reaction difficult to control. This results in a low grafting rate, unstable material properties, and a short residence time. The MAH grafting reaction is inefficient, resulting in a low grafting rate. Furthermore, the corrosion of MAH on extrusion equipment limits the commercial production of MAH-grafted polyolefins (PP-g-MAH).
[0112] The epoxy curing agent is bisphenol A epoxy resin. The lubricant is stearic acid, and the phenolic antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]. The amount of stearic acid used is 0.1 parts, and the amount of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate used is 0.08 parts per 100 parts of the acid-modified polypropylene.
[0113] The bonding composition had a melting temperature of 70° C. and an SP value of 8.2.
[0114] In this embodiment, a metal composite film is prepared by referring to the preparation method of the metal composite film provided in Example 1, with the only difference being that the inner bonding layer is prepared using the bonding composition provided in this embodiment.
[0115] Performance test results of the metal composite film:
[0116] The metal composite film exhibited excellent electrolyte resistance after being stored at 85°C for 14 days in an electrolyte containing 1000ppm water. Its peel strength was 11.56N after 28 days of storage, reaching 4.08N. Heat seal strength was also tested at 120°C for 5 minutes, reaching 55.93N, with a seal strength retention rate of 47%. This demonstrates excellent high-temperature resistance.
[0117] Example 4
[0118] An embodiment of the present invention provides an adhesive composition for battery packaging materials, wherein the raw materials of the adhesive composition are composed of acid-modified polypropylene, an isocyanate curing agent, a phosphite containing a hindered aromatic group, a phenolic antioxidant, a lubricant, and a crystallization accelerator.
[0119] The acid-modified polypropylene had a weight-average molecular weight of 97,000 and two melting peaks. These two melting peaks were observed when a differential scanning calorimeter was used to measure the calorific value relative to the heating time at a temperature increase of 10°C / min and at least two locations exhibited endothermic activity derived from the acid-modified polypropylene.
[0120] Specifically, TAp_1 is 158.38°C, TAp_2 is 104.3°C, Ap_2 / Ap_1 is 45%, TmAp1 is 135-170°C, and TmAp2 is 75-130°C.
[0121] The preparation method for this acid-modified polypropylene is as follows: melt grafting is employed. The melt grafting method has been a common method for grafting modified PP in recent years. This process involves co-extrusion of PP and maleic anhydride (MAH) initiator under certain conditions. The reaction takes place above the melting point of PP, typically at 190-230°C. The reaction is simple to operate and requires no solvent recovery, enabling industrial continuous production. However, due to the high reaction temperature, the PP chain is prone to scission, resulting in significant degradation of macromolecular free radicals in the melt-grafted PP system with small molecule initiators (such as diisobutylene peroxide), making the reaction difficult to control. The product also suffers from a low grafting rate, unstable material properties, and a short residence time. The MAH grafting reaction is inefficient, resulting in a low grafting rate. Furthermore, the corrosion of MAH on extrusion equipment limits the commercial production of MAH-grafted polyolefins (PP-g-MAH).
[0122] The mass ratio of acid-modified polypropylene to isocyanate curing agent is 100:2. The isocyanate curing agent contains at least 50% of at least one of hexamethylene diisocyanate (HDI) or pentamethylene diisocyanate (PDI), or a mixture of at least 50% of hexamethylene diisocyanate (HDI) and pentamethylene diisocyanate (PDI). The hindered aromatic phosphites are octadecanol-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and tris(2,4-di-tert-butyl)phenyl phosphite. The amount of octadecanol-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate is 0.1 part, and the amount of tris(2,4-di-tert-butyl)phenyl phosphite is 0.1 part per 100 parts of the acid-modified polypropylene. The lubricants are calcium stearate and polyethylene wax, with the amount of calcium stearate being 0.2 part and the amount of polyethylene wax being 0.2 part respectively. The crystallization promoter is sodium 2,2'-methylenebis(4,6-di-tert-butylphenyl) phosphate, and the amount used is 0.05 parts. The amount used of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate is 0.05 parts.
[0123] The bonding composition had a melting temperature of 60° C. and an SP value of 8.0.
[0124] In this embodiment, a metal composite film is prepared by referring to the preparation method of the metal composite film provided in Example 1, with the only difference being that the inner bonding layer is prepared using the bonding composition provided in this embodiment.
[0125] Performance test results of the metal composite film:
[0126] The metal composite film exhibited excellent electrolyte resistance after being stored at 85°C for 14 days in an electrolyte containing 1000ppm water. After 28 days, the film exhibited an electrolyte peel strength of 4.12N. Heat seal strength was measured at 120°C for 5 minutes and the seal retention rate was 45%. This demonstrates excellent high-temperature resistance.
[0127] Example 5
[0128] An embodiment of the present invention provides an adhesive composition for battery packaging materials, wherein the raw materials of the adhesive composition are composed of acid-modified polypropylene, an epoxy curing agent, a phosphite containing a hindered aromatic group, a phenolic antioxidant, a lubricant, and a crystallization accelerator.
[0129] The acid-modified polypropylene has a weight-average molecular weight of 102,000 and two melting peaks: TAp_1 of 155.9°C, TAp_2 of 103°C, Ap_2 / Ap_1 of 40%, TmAp1 of 135-170°C, and TmAp2 of 75-130°C.
[0130] The preparation method for this acid-modified polypropylene is as follows: The polypropylene is first dissolved in a boiling toluene, xylene, or benzene solution at 100-140°C, followed by the addition of monomers and a flammable agent for grafting. The grafted product is then extracted with acetone to remove unreacted monomers, forming the final product. This method offers a low reaction temperature, minimal side reactions, low PP degradation, and high grafting efficiency. The method is simple and suitable for small-batch production.
[0131] The mass ratio of acid-modified polypropylene to epoxy curing agent is 100:4. The epoxy curing agent is a mixture of bisphenol F epoxy resin and novolac epoxy resin in a mass ratio of 9:1. The hindered aromatic phosphites are octadecanol-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and tris(2,4-di-tert-butyl)phenyl phosphite. For every 100 parts of the acid-modified polypropylene, the amount of octadecanol-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and tris(2,4-di-tert-butyl)phenyl phosphite is 0.05 parts, and the amount of tris(2,4-di-tert-butyl)phenyl phosphite is 0.05 parts. The lubricant is oleamide, and the amount of oleamide is 0.6 parts. The crystallization promoter is 2,2'-methylenebis(4,6-di-tert-butylphenyl) sodium phosphate, the amount of which is 0.02 parts, and the amount of the phenolic antioxidant N,N"-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine is 0.1 parts.
[0132] The bonding composition had a melting temperature of 65° C. and an SP value of 8.0.
[0133] In this embodiment, a metal composite film is prepared by referring to the preparation method of the metal composite film provided in Example 1, with the only difference being that the inner bonding layer is prepared using the bonding composition provided in this embodiment.
[0134] Performance test results of the metal composite film:
[0135] The metal composite film exhibited excellent electrolyte resistance after being stored at 85°C for 14 days in an electrolyte containing 1000ppm water. After 28 days, the film exhibited an electrolyte peel strength of 4.0N. Heat seal strength was measured at 120°C for 5 minutes and was 47.2N, with a seal strength retention rate of 44%. This demonstrates excellent high-temperature resistance.
[0136] Comparative Example 1
[0137] An embodiment of the present invention provides an adhesive composition for battery packaging materials, wherein the raw materials of the adhesive composition are composed of acid-modified polypropylene, an epoxy curing agent, a phosphite containing a hindered aromatic group, a phenolic antioxidant, a lubricant, and a crystallization accelerator.
[0138] The acid-modified polypropylene has a weight average molecular weight of 250,000 and two melting peaks. TAp_2 is 85.44°C, TAp_1 is 55°C, and Ap_2 / Ap_1 is 60%. Figure 2 .
[0139] In this embodiment, a metal composite film is prepared by referring to the preparation method of the metal composite film provided in Example 1, with the only difference being that the inner bonding layer is prepared using the bonding composition provided in this embodiment.
[0140] Performance test results of the metal composite film:
[0141] The metal composite film exhibited a peel strength of 9.5N after 14 days of storage at 85°C in an electrolyte containing 1000ppm water. After 28 days, the peel strength was 2.8N. This electrolyte resistance dropped below 10N after 14 days and below 3N after 28 days, indicating poor electrolyte resistance. Heat seal strength was measured at 120°C for 5 minutes and was 27.74N, with a seal strength retention rate of 23%. High-temperature resistance was only half that of Example 1, indicating poor performance.
[0142] Comparative Example 2
[0143] An embodiment of the present invention provides an adhesive composition for battery packaging materials, wherein the raw materials of the adhesive composition are composed of acid-modified polypropylene, an epoxy-based curing agent, and a phosphite containing a hindered aromatic group.
[0144] Among them, the weight average molecular weight of the acid-modified polypropylene is 60,000, and the TAp_1 is 100.79℃.
[0145] The hindered aromatic group-containing phosphites are octadecanol-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and tris(2,4-di-tert-butyl)phenyl phosphite. Relative to every 100 parts of the acid-modified polypropylene, the amount of octadecanol-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate is 0.1 part, and the amount of tris(2,4-di-tert-butyl)phenyl phosphite is 0.15 part.
[0146] In this embodiment, a metal composite film is prepared by referring to the preparation method of the metal composite film provided in Example 1, with the only difference being that the inner bonding layer is prepared using the bonding composition provided in this embodiment.
[0147] Performance test results of the metal composite film:
[0148] After 14 days of storage at 85°C in an electrolyte containing 1000ppm water, the electrolyte peel strength was 12.61N. After 28 days, the electrolyte peel strength was 2.9N. While the electrolyte resistance remained strong after 14 days, it dropped below 3N after 28 days, indicating poor electrolyte resistance. Heat seal strength after 5 minutes of storage at 120°C was 35.54N, with a heat seal strength retention rate of 31%. High-temperature resistance was significantly lower than that of Example 1, indicating poor heat resistance.
[0149] Comparative Example 3
[0150] An embodiment of the present invention provides an adhesive composition for battery packaging materials, wherein the raw materials of the adhesive composition are composed of acid-modified polypropylene and an isocyanate curing agent.
[0151] The acid-modified polypropylene has a weight-average molecular weight of 58,000 and two melting peaks: TAp_1 at 78°C, TAp_2 at 63°C, and Ap_2 / Ap_1 at 40%.
[0152] The mass ratio of the acid-modified polypropylene solution to the isocyanate curing agent is 110:1, the cyanate curing agent is PDI, and the lubricant is a fatty acid ester, with a content of 0.2 parts of the fatty acid ester per 100 parts of the acid-modified polypropylene.
[0153] In this embodiment, a metal composite film is prepared by referring to the preparation method of the metal composite film provided in Example 1, with the only difference being that the inner bonding layer is prepared using the bonding composition provided in this embodiment.
[0154] Performance test results of the metal composite film:
[0155] After 14 days of storage at 85°C in an electrolyte containing 1000ppm water, the electrolyte peel strength was 8.99N. After 28 days, the peel strength was 0.35N. Electrolyte resistance decreased significantly after 14 days, and after 28 days, the adhesive strength was almost non-existent, indicating poor electrolyte resistance. Heat seal strength was tested at 120°C for 5 minutes and was 7.47N, with a heat seal strength retention rate of 6%. High-temperature resistance was almost non-existent at 120°C, indicating poor heat resistance.
[0156] The performance test results of the metal composite films of Examples 1-3 and Comparative Examples 1-3 are summarized in Figure 3 .
[0157] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are intended to be within the scope of protection of the present invention.
Claims
1. A bonding composition for battery packaging materials, characterized in that: The raw materials include acid-modified polypropylene and additives, wherein the acid-modified polypropylene exhibits at least two melting peaks during the heating process when tested by differential scanning calorimetry, specifically: (1) The endothermic temperature of the first main melting peak, TmAp1, ranges from 135 to 170 °C, and its corresponding peak area is recorded as Ap_1; (2) The endothermic temperature of the second melting peak, TmAp2, ranges from 75 to 130 °C, and its corresponding peak area is recorded as Ap_2; (3) The area ratio of the peak area Ap_2 of the second melting peak to the peak area Ap_1 of the first main melting peak satisfies: Ap_2 / Ap_1≤60%.
2. The adhesive composition for battery packaging materials according to claim 1, characterized in that: The temperature of the top peak in the endothermic temperature band of the first main melting peak is set as TAp_1, and TAp_1 is above 140°C; The temperature of the top peak in the endothermic temperature band of the peak temperature of the second melting peak is defined as TAp_2, and TAp_2 is 99.6°C or higher.
3. The adhesive composition for battery packaging materials according to claim 1 or 2, characterized in that: The calorific value of the acid-modified polypropylene during the heating time was determined by differential scanning calorimetry with the heating condition set at 5-10°C / min.
4. The adhesive composition for battery packaging materials according to claim 1, characterized in that: Its raw materials are composed of acid-modified polypropylene, epoxy curing agent, phosphite containing hindered aromatic group, phenolic antioxidant, lubricant and crystallization accelerator; or Its raw materials are composed of acid-modified polypropylene and isocyanate curing agent.
5. The adhesive composition for battery packaging materials according to claim 4, characterized in that: The hindered aromatic group-containing phosphite is at least one selected from octadecanol-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, bis(2,4-di-tert-butylphenol) pentaerythritol diphosphite, tris(2,4-di-tert-butyl)phenyl phosphite, (2,4,6-tri-tert-butylphenyl-2-butyl-2-ethyl)-1,3,2,2'-ethylenebis(4,6-di-tert-butylphenyl) fluorophosphite, tetrakis(2,4-di-tert-butyloctaalkoxy-4,4-biphenyl) phosphate and spiroethylene glycol di[2,2'-methylenebis(4,6-di-tert-butylphenyl)]phosphite; preferably at least one of octadecanol-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and tris(2,4-di-tert-butyl)phenyl phosphite; Preferably, the amount of the hindered aromatic phosphite is 0.05-0.35 parts per 100 parts of the acid-modified polypropylene, in parts by weight; Preferably, based on parts by weight, for every 100 parts of the acid-modified polypropylene, the amount of octadecanol-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate is 0.05-0.2 parts, and the amount of tris(2,4-di-tert-butyl)phenyl phosphite is 0.05-0.15 parts.
6. The adhesive composition for battery packaging materials according to claim 4, characterized in that: The phenolic antioxidant includes at least one of N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, 3-(3,5-di-tert-butyl-4-hydroxy)-N'-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]propionohydrazide, 2,6-di-tert-butyl-4-methylphenol, bis(3,5-di-tert-butyl-4-hydroxyphenyl)sulfide, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and tert-butylhydroquinone; preferably pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]; Preferably, the amount of the phenolic antioxidant is less than 0.1 parts by weight per 100 parts by weight of the acid-modified polypropylene.
7. The adhesive composition for battery packaging materials according to claim 4, characterized in that: The lubricant is selected from at least one of amide derivatives, diatomaceous earth, talc, silicon dioxide, calcium carbonate, calcium sulfate, organosiloxane compounds and stearates; more preferably at least one of oleamide, erucamide, calcium stearate and polyethylene wax; Preferably, the amount of the lubricant is 0.1-0.6 parts by weight per 100 parts of the acid-modified polypropylene.
8. The adhesive composition for battery packaging materials according to claim 4, characterized in that: The crystallization promoter is at least one selected from the group consisting of metal phosphates, basic metal phosphates, and composites thereof, preferably sodium 2,2'-methylenebis(4,6-di-tert-butylphenyl) phosphate and basic aluminum 2,2'-methylenebis(4,6-di-tert-butylphenyl phosphate); more preferably sodium 2,2'-methylenebis(4,6-di-tert-butylphenyl) phosphate; Preferably, the amount of the crystallization accelerator is 0.02-0.1 parts per 100 parts of the acid-modified polypropylene, calculated by weight.
9. The adhesive composition for battery packaging materials according to claim 4, characterized in that: The epoxy curing agent is selected from at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, phenol novolac epoxy, o-cresol novolac epoxy, trisphenol methane type and tetraphenol ethane type epoxy, polyphenol glycidyl ether epoxy resin, aliphatic glycidyl ether epoxy resin and glycidyl ester epoxy resin, preferably at least one of bisphenol A epoxy resin, bisphenol F epoxy resin and novolac epoxy resin, more preferably bisphenol F epoxy resin and novolac epoxy resin; Preferably, the epoxy curing agent is used in an amount of 2-15 parts by weight for every 100 parts of the acid-modified polypropylene.
10. The adhesive composition for battery packaging materials according to claim 9, characterized in that: The epoxy value of the epoxy curing agent is 0.2 mol / 100g-2.0 mol / 100g; Preferably, the mass ratio of the bisphenol F epoxy resin to the novolac epoxy resin is (7-10):
1.
11. The adhesive composition for battery packaging materials according to claim 4, characterized in that: The isocyanate curing agent is selected from at least one of hexamethylene diisocyanate or pentamethylene diisocyanate containing more than 50%; Preferably, the amount of the isocyanate curing agent used is 1-4 parts by weight for every 100 parts of the acid-modified polypropylene.
12. The adhesive composition for battery packaging materials according to claim 1, characterized in that: The SP value of the bonding composition is 7.6-8.6; Preferably, the dissolution temperature of the bonding composition is 60-70°C.
13. A metal composite film for battery packaging material, characterized in that: It comprises an outer layer, an outer adhesive layer, a metal layer, an inner adhesive layer and a hot-melt resin layer arranged in sequence, wherein the inner adhesive layer is prepared by the adhesive composition for battery packaging material according to any one of claims 1 to 12.
14. A soft package shell, characterized in that: It is prepared by the metal composite film for battery packaging material according to claim 13.
15. A battery, characterized in that: It comprises the soft package shell according to claim 14.